Comparison Of Islamic Education Modernization Of Imam Hatip Anatolian Turkish School With Al-Azhar Islamic School 9 Yogyakarta Indonesia (Al-I'tibar : Jurnal Pendidikan Islam, 2024)
The Imam Hatip School is the focus of modern Islamic education by Turkish society. In addition, the purpose of the study is to prove that Islamic schools in Turkey modernize Islamic education in Imam Hatip schools. Of course, Islamic educational institutions present an education system that produces students who have general knowledge and are supported by good religious knowledge. Al-Azhar Islamic High School 9 Yogyakarta Islamic education still maintains its religious identity in the same way as Islamic boarding schools and madrasas, but there are some that have carried out a renewal agenda in response to the guidance of modern times. The consequence of Islamic school education is with high school administration in the modern Islamic Religious Education system today. The modernization of Islamic education in Turkey and Indonesia cannot be separated from the role of reformers who received enlightenment from the modernization movement in the field of education. The modernization aspects that need to be considered in educational institutions include: by adding modern science and Islamic religious science.